A woman in Jerusalem - Yehoshua, Abraham B.; Halkin, Hillel, 1939- (Orlando : Harcourt, Inc., 2006)
A woman in her forties is a victim of a suicide bombing at a Jerusalem market. Her body lies nameless in a hospital morgue. She had apparently worked as a cleaning woman at a bakery, but there is no record of her employment. When a Jerusalem daily accuses the bakery of "gross negligence and inhumanity toward an employee," the bakery's owner, overwhelmed by guilt, entrusts the task of identifying and burying the victim to a human resources man. This man is at first reluctant to take on the job, but as the facts of the woman's life take shape--she was an engineer from the former Soviet Union, a non-Jew on a religious pilgrimage to Jerusalem, and, judging by an early photograph, beautiful--he yields to feelings of regret, atonement, and even love.--From publisher description.
Keywords: Victims of terrorism -- Israel -- Fiction; Gentiles -- Israel -- Fiction; Jerusalem -- Fiction; Psychological fiction